2018
DOI: 10.1186/s12891-018-2034-6
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion and exclusion criteria used in non-specific low back pain trials: a review of randomised controlled trials published between 2006 and 2012

Abstract: BackgroundLow back pain is a common health complaint resulting in substantial economic burden. Each year, upwards of 20 randomised controlled trials (RCTs) evaluating interventions for non-specific low back pain are published. Use of the term non-specific low back pain has been criticised on the grounds of encouraging heterogeneity and hampering interpretation of findings due to possible heterogeneous causes, challenging meta-analyses. We explored selection criteria used in trials of treatments for nsLBP.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…CPM was impaired compared to controls in those studies with high patient-reported pain intensities (SMD=-0.63[-0.96, -0.31], Z=3.78, P<0.001), but not in those with low pain intensities (SMD=-0.10 [-0.30, 0.10], Z=0.95, P=0.34). Pain severity thus impacted the magnitude of impairment in CPM (X2 1 =7.40, P<0.01).Consistent with this, a moderate association was observed between mean pain severity and between-group SMD in CPM (R s =-0.538, P=0.021), suggesting higher pain severity was associated with greater impairment in CPM compared to controls.It should be noted that pain severity was not correlated with pain duration (R S =0.087, P>0.61), so these results should not be interpreted as reflective of the same relationship. Further, among studies with available data for both CPM and TSP (n = 6), these variables were not correlated (R S = 0.143, P>0.75).Adequate data was available to compare studies assessing CPM using cold (n = 13) versus hot (n = 4) conditioning stimuli, though this factor did not significantly alter magnitude of CPM impairment This was expected, given the known heterogeneity in sampling, study sizes, modalities and protocols.DISCUSSIONThis paper presents the most extensive systematic review and meta-analysis of CPM and TSP data in LBP patients compared to controls to date.…”
supporting
confidence: 68%
“…CPM was impaired compared to controls in those studies with high patient-reported pain intensities (SMD=-0.63[-0.96, -0.31], Z=3.78, P<0.001), but not in those with low pain intensities (SMD=-0.10 [-0.30, 0.10], Z=0.95, P=0.34). Pain severity thus impacted the magnitude of impairment in CPM (X2 1 =7.40, P<0.01).Consistent with this, a moderate association was observed between mean pain severity and between-group SMD in CPM (R s =-0.538, P=0.021), suggesting higher pain severity was associated with greater impairment in CPM compared to controls.It should be noted that pain severity was not correlated with pain duration (R S =0.087, P>0.61), so these results should not be interpreted as reflective of the same relationship. Further, among studies with available data for both CPM and TSP (n = 6), these variables were not correlated (R S = 0.143, P>0.75).Adequate data was available to compare studies assessing CPM using cold (n = 13) versus hot (n = 4) conditioning stimuli, though this factor did not significantly alter magnitude of CPM impairment This was expected, given the known heterogeneity in sampling, study sizes, modalities and protocols.DISCUSSIONThis paper presents the most extensive systematic review and meta-analysis of CPM and TSP data in LBP patients compared to controls to date.…”
supporting
confidence: 68%
“…It was prospectively registered, and incorporated design features known to minimise bias such as concealed allocation, and an intention-to-treat analysis. The participants were highly representative of people with disabling LBP in clinical practice, compared with most LBP trials which have very narrow inclusion criteria 55. The same trial physiotherapists delivered both interventions, minimising differences in clinician expertise and communication style confounding the results.…”
Section: Discussionmentioning
confidence: 99%
“…Participants will be aged 18 to 65 years, male, female or of indeterminate sex, proficient in English, have a history of chronic nonspecific LBP as confirmed by a general practitioner (GP), and report a score of 3 or greater for their chronic nonspecific LBP on the numeric pain rating scale to ensure a minimally clinically important change for this score can be measured [ 29 ]. The chronic nonspecific LBP will need to be located between the ribs and buttock creases to be eligible [ 30 ]. Participants will be excluded if they have significant or worsening signs of neurological deficit, inflammatory joint disease, are pregnant, or have previous (within the last 12 months) or current use of foot orthotic devices.…”
Section: Methodsmentioning
confidence: 99%